EPIDEMIOLOGIC PROFILE OF HIV CHILDREN AND ADOLESCENTS IN A REFERENCE HOSPITAL FOR THE TREATMENT OF AIDS - NATAL/RN/BRAZIL (Fiep Bulletin - online, 2013)
The gradual increase in the number of AIDS cases among women of all Brazilian regions in the vast majority through sexual transmission, has contributed significantly to the increase of HIV vertical transmission infection, raising the number of cases of AIDS in teenagers. This study objective was tracing the epidemiological profile of children and adolescents suffering from HIV / AIDS met in a public service for the AIDS treatment in Natal-RN. It is an epidemiological analytical study, descriptive and quantitative, developed at the ambulatory of Giselda Trigueiro Hospital (HGT), reference to treat AIDS, located in Natal - RN / Brazil. The sample was composed of 33 children and adolescents suffering from HIV, attended in this reference center. As main results, it was observed that children and adolescents were at the interval between the 03 and 14 years, with an average age of 8.5 years, being 20 (60.3%) females and 13 (39.4%) males. It was identified that most of them, 18 (54.55%), were from Natal. The group had as means of transmission, the vertical in 31 (93.93%), except to 2 cases (6.07%), which occurred through blood transfusion. It was found that 30 (90.9%) of teenagers were fed with breast milk after birth. Regarding education, 19 (86.36%) had been enrolled in institutions of public education and 3 (13.64%) in private institutions. It follows, therefore, that the occurrence of AIDS in this age group is directly linked to the diagnosis in women, as well as the non-adoption of chemo-prophylactics measures during pregnancy, childbirth and puerperium, as well as non-inhibiting lactation.
Keywords: AIDS / HIV; Children; Adolescents.